Growth response ofTheobroma cacao L. seeldings to inoculation with vesicular-arbuscular mycorrhizal fungi - Chulan (Hashim), Azizah; Ragu, P. (Springer, 1986)
The effects of vesicular-arbuscular mycorrhiza (VAM) on the growth and phosphorus uptake of cocoa seedlings (Theobroma cacao L.) grown for 100 days in polythene bags, were studied at five levels of phosphorus fertilization in both steamed and unsterile Bungor Series soil (a fine clayey, kaolinitic isohyperthermic Typic Paleudult).